Branching pattern in the evolutionary tree for human mitochondrial DNA. - Di Rienzo, A (1991)
Eighty-eight types of mitochondrial (mt) DNA were found by sequencing the most variable part of the control region from 117 Caucasians. In the tree relating those types, most of the branching events occur about two-thirds of the way from the root of the tree to the tips of the branches. Moreover, the distribution of sequence differences between all possible pairs of individuals is approximately Poisson. Other non-African populations show a similar pattern. Assuming a neutral model, these findings imply that the probability of survival of new lineages has undergone dramatic changes, probably due to population expansion. Conversely, African populations show multimodal distributions fitting with a model of constant population size.